2010
DOI: 10.1177/0960327110393764
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sodium aescinate on lung injury induced by methyl parathion

Abstract: Methyl parathion (MP) is a high venenosus insecticide. It has been used in pest control of agriculture for several years. The present study is performed to investigate the protective effect of sodium aescinate (SA) on lung injury induced by MP. Forty male Sprague-Dawley rats are randomly divided into five groups, with 8 animals in each group: control group, MP administration group, MP plus SA at doses of 0.45 mg/kg, 0.9 mg/kg and 1.8 mg/kg groups. Acetylcholinesterase (AChE) activity and nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Thus, the effects of SA on myocardial apoptosis induced by MP have also been investigated.. Sodium aescinate could also protect against lung injury induced by intestinal ischemia/reperfusion (I/R) by regulating the expression of Bcl-2 and Bax proteins and inhibiting the apoptosis of lung cells [9]. This research demonstrate that SA can exert cardio-protective effect by inhibiting MP-induced apoptosis of myocardial cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the effects of SA on myocardial apoptosis induced by MP have also been investigated.. Sodium aescinate could also protect against lung injury induced by intestinal ischemia/reperfusion (I/R) by regulating the expression of Bcl-2 and Bax proteins and inhibiting the apoptosis of lung cells [9]. This research demonstrate that SA can exert cardio-protective effect by inhibiting MP-induced apoptosis of myocardial cells.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the effects of SA in clinics include antiinflammation, anti-oxidation, and regulation of microcirculation [8]. Researchers found that SA can attenuate MP-induced lung injury via antiinflammatory and anti-oxidative effects [9]. However, the effects of SA on MP-induced myocardial injury remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SA has potent anti-inflammatory, anti-edematous and anti-oxidative activity by enhancing glucocorticoid and its receptor expression (Du et al, 2011; Montopoli et al, 2007; Wang et al, 2009; Wang et al, 2012; Wei et al, 2011; Xin et al, 2011; Yang et al, 2011). Accordingly, the effect of SA treatment on the PGPS-induced inflammation was investigated in Tlr2 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…4 It is also reported that the organophosphorus-treated rats showed lung injury characterized by oxidative stress and inflammation. 5 Panax ginseng Meyer is a well-known medicinal plant from eastern Asian countries, especially China, Korea, and Japan. Ginsenosides are the bioactive ingredients of ginseng that is used widely in traditional medicine.…”
Section: Introductionmentioning
confidence: 99%